Analysis of Learning Effectiveness During the Covid-19 Pandemic at Korwilcam Bidik Elementary School, Adimulyo District, Kebumen Regency - Fajar Sugiharto; Rahmat Mulyono (PT Publikasiku Academic Solution, 2023)
The objectives of this study were (1) to analyze the learning approach in the primary school Korwilcam Bidik, Adimulyo District, Kebumen Regency in the Academic Year 2020/2021 during the Covid-19 pandemic, (2) to analyze learning management at the Korwilcam Bidik primary school, Adimulyo District, Kebumen Regency in Academic Year 2020/2021 during the Covid-19 pandemic (3) to analyze the obstacles that arise and how to overcome them in learning at the Korwilcam Bidik elementary school, Adimulyo District, Kebumen Regency in the 2020/2021 Academic Year during the Covid-19 pandemic (4) to analyze the effectiveness of learning in the primary school Korwilcam Bidik, Adimulyo Subdistrict, Kebumen Regency in the Academic Year 2020/2021 during the Covid-19 pandemic. This research method uses qualitative research, using interview techniques, observation and documentation. In this study the researchers explored and found the teaching approach chosen by the teacher, why the teacher chose that approach, analyzed learning management, the obstacles that arise in learning and how to overcome these obstacles and analyzed qualitatively the effectiveness of learning carried out by teachers at Korwicam Bidik, Adimulyo District, Kebumen Regency. . Analysis using the Miles and Hubermen model. Researchers collect data, reduce, present, verify data and draw conclusions. The results of the study (1) teachers at Korwilcam Bidik, Adimulyo District during the Covid-19 pandemic, their learning used online, offline and a combination of online and offline approaches. (2) good category learning management (3) learning constraints in the form of device availability, network disruption, availability internet packages, student discipline and inadequate competence in technology and teacher information, the constraints are overcome by the teacher by paying attention to the causes of these constraints. (4) based on the analysis of the learning effectiveness indicators, the learning carried out by the teachers at the Korwilcam Bidik, Adimulyo District was effective.